Assessment of ear metric properties in young Turkish adults - PETEKKAYA, Emine; ÖZANDAÇ POLAT, Sema; KABAKCI, Ayşe Gül; ÇEVİK, Yiğit (SelSistem, 2020)
Aim: The ear is a critical component of the human face functionally and aesthetically. Studies in recent years have reported that the morphological properties of the outer ear show substantial differences based on sex and ethnic group. The data obtained in these studies are guiding for plastic surgeons. Methods: This cross-sectional study was carried out on a Turkish population. Ear axis, antihelix angle, ear length, ear width, earlobe length and earlobe width measurements were made on 191 healthy adult volunteers (106 women, 85 men) between the ages of 18-25 years. Ear metric values mentioned above were compared between the genders, and correlation analysis was conducted for all. Results: All values except the antihelix angle were larger in males (P=0.0486; P<0.001; P=0.004; P<0.001; P=0.038 for ear axis, length, width, ear lobule length and width respectively). The ear axis was positively correlated with the antihelix angle, the ear width and the ear lobule width and the ear length was positively correlated with the ear width and ear lobule length (P<0.001 for both). Conclusion: Although our study has some limitations it includes noteworthy data about outer ear metric values of the young adult Turkish population which we believe is going to be beneficial to standardization and optimization in ear surgery.